Inclusion of LGBTI+ Persons in Workplaces in Thailand - World Bank (World Bank, Washington, DC, 2022)
Thailand is widely considered progressive among developing and middle-income countries regarding the inclusion of lesbian, gay, bisexual, transgender, or intersex (LGBTI+) people. Thailand has made progress in developing legislation to stop LGBTI+ discrimination, including adopting the Gender Equality Act of 2015, which makes it illegal to discriminate against people who look different in appearance from their sex at birth. Despite proactive steps toward inclusion the country has taken to date, however, LGBTI+ people continue to experience discrimination, limited job and housing opportunities, barriers to accessing many common services, and other challenges in Thailand, with each subgroup affected differently.